2021
DOI: 10.3390/math9101122
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Model for Time Series of Complex Structure with ARIMA Components

Abstract: A hybrid model for the time series of complex structure (HMTS) was proposed. It is based on the combination of function expansions in a wavelet series with ARIMA models. HMTS has regular and anomalous components. The time series components, obtained after expansion, have a simpler structure that makes it possible to identify the ARIMA model if the components are stationary. This allows us to obtain a more accurate ARIMA model for a time series of complicated structure and to extend the area for application. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…In statistical stage, exponential smoothing [4], Kalman filter [5] and auto-regression (AR) [6]. The AR is a basic method [7] and some improved methods have been proposed, such as auto-regressive moving average (ARMA) [8], auto-regressive integrated moving average (ARIMA) [9,10] and other forms [11,12], which have widely applied to time series forecasting in different fields [10,12,13]. The traditional methods are more suitable for the stable time series, but the sunspot a Correspondence to: Nian Fu.…”
Section: Introductionmentioning
confidence: 99%
“…In statistical stage, exponential smoothing [4], Kalman filter [5] and auto-regression (AR) [6]. The AR is a basic method [7] and some improved methods have been proposed, such as auto-regressive moving average (ARMA) [8], auto-regressive integrated moving average (ARIMA) [9,10] and other forms [11,12], which have widely applied to time series forecasting in different fields [10,12,13]. The traditional methods are more suitable for the stable time series, but the sunspot a Correspondence to: Nian Fu.…”
Section: Introductionmentioning
confidence: 99%
“…Classical approaches, such as median construction, regression models, spectral methods etc., widely used for data analysis, do not allow one to detect and to analyze ionospheric anomalies with sufficient effectiveness [2,3,9]. At the present time, modern methods from Data Mining set are being developed to investigate ionospheric data [8,[10][11][12][13]. They make it possible to obtain new knowledge from complex data applying non-conventional approaches and their combinations.…”
Section: Introductionmentioning
confidence: 99%
“…In the paper [8], the authors showed the possibility to combine wavelet filtering with NARX neural networks [14] for detection of anomalous periods in ionopspheric data. In earlier papers [10,15], computational solutions based on discrete wavelet transform and adaptive thresholds were proposed for ionospheric anomaly detection and analysis. In this paper we continue this investigation and propose a complex approach.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we propose to use the approach developed by the authors [31][32][33]. It is based on wavelet transform, which allows us to investigate complicated nonstationary changes in geophysical data and is widely used in physics, in particularly, in geophysics [4,7,9,26,[34][35][36][37][38]. Based on the wavelet transform, we proposed an automated method to detect geomagnetic pulsations [34,35], constructed an algorithm for automatic detection of magnetic storms with increased risk of occurrence of geomagneticallyinduced currents [3], and developed a method to calculate the geomagnetic activity index WISA [36,38].…”
Section: Introductionmentioning
confidence: 99%